Evaluation of the new continuous mononuclear cell collection protocol versus an older version on two different apheresis machines. Issue 7 (6th May 2018) - Spoerl, Silvia; Wäscher, Dagmar; Nagel, Stefanie; Peschel, Christian; Verbeek, Mareike; Götze, Katharina; Krackhardt, Angela M.
Abstract : BACKGROUND: Cell separators are routinely used to collect CD34 + blood stem cells in the context of customized stem cell transplantation procedures. The Spectra Optia (Terumo BCT) is a novel development of the precursor instrument, the Cobe Spectra (Terumo BCT). STUDY DESIGN AND METHODS: In this report, 146 autologous and 42 allogeneic donors undergoing apheresis on the Cobe Spectra using the mononuclear cell (MNC) program 4.7 or on the Spectra Optia using the new continuous mononuclear cell (cMNC) program 11.2 are compared. RESULTS: Viability of cells and collection efficacy within the apheresis products was comparable for autologous and allogeneic products collected with the MNC or cMNC method. However, we found a reduced duration of the apheresis procedure and lower hematocrit within the apheresis products when using the cMNC in autologous and allogeneic donors. Moreover, allogeneic donors collected substantially more CD34 + cells per kilogram of body weight when using the cMNC method. Differences in platelets before and after apheresis were substantially smaller in this cohort when compared to the cohort collected with the MNC method. Neutrophil and platelet engraftment after autologous or allogeneic transplantation with a product collected with the MNC procedure was comparable to a transplantation with a product processed according to the cMNC method. CONCLUSION: Comparison of the MNC (Cobe Spectra) and the cMNC (Spectra Optia) methods demonstrated an equal performance and outcome. However, advantages were present using the cMNC method with respect to apheresis duration and hematocrit within the apheresis product (autologous/allogeneic donors) and numbers of CD34 + cells collected, especially in allogeneic donors.